2011
DOI: 10.1162/pres_a_00052
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality Version of the Trier Social Stress Test: A Pilot Study

Abstract: One of the most common methods of inducing stress in the laboratory in order to examine the stress response in healthy and clinical populations is the Trier Social Stress Test (TSST). Briefly, the participant is asked to deliver a speech and to perform an arithmetic task in front of an evaluating committee. The committee, consisting of three trained actors, does not respond emotionally during the test, which makes the situation very stressful for the participant. One disadvantage of the TSST is that it can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…This increase is slightly lower than the ones reported by Kirschbaum et al (1993) and Kotlyar et al (2008) for the original TSST (24 -34% and 30% respectively). In their studies using a CAVE, Jönsson et al (2010) reported an increase of 17% during verbal contribution and an increase of 22% during the arithmetic task, while Wallergaard et al (2011) could only find an increase of 12% during the speech task and 9% during the arithmetic task. Using a HMD, Shiban et al (2016) found an increase of 12% in the speech and 10% in the arithmetic task.…”
Section: Peripher-physiological Measurementsmentioning
confidence: 93%
See 1 more Smart Citation
“…This increase is slightly lower than the ones reported by Kirschbaum et al (1993) and Kotlyar et al (2008) for the original TSST (24 -34% and 30% respectively). In their studies using a CAVE, Jönsson et al (2010) reported an increase of 17% during verbal contribution and an increase of 22% during the arithmetic task, while Wallergaard et al (2011) could only find an increase of 12% during the speech task and 9% during the arithmetic task. Using a HMD, Shiban et al (2016) found an increase of 12% in the speech and 10% in the arithmetic task.…”
Section: Peripher-physiological Measurementsmentioning
confidence: 93%
“…Both, mean cortisol habituation and dissociated stress habituation patterns between the SAM and the HPA response systems to repeated TSST provocations are well-known findings (Schommer et al, 2003;Wüst et al, 2005). Wallergaard et al (2011) also used a CAVE-system to examine the VR-TSST (Wallergaard et al, 2011). Heart rates showed an average increase that was comparable to the conventional TSST (24-34%, (Kirschbaum et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zanbaka, Ulinski, Goolkasian, and Hodges (2004) showed in a social facilitation/inhibition experiment that the presence of a virtual human-affected participants' performance in the same way as the presence of a real human. The TSST has been programmed in virtual settings before, and the virtual version evoked physiological responses (heart rate and cortisol) that were comparable with the responses found in real-life versions of the TSST (Jönsson, et al, 2010;Wallergård, Jönsson, Österberg, Johansson, & Karlson, 2011). IVET is also used as an effective treatment to remedy fear of public speaking (e.g., North, North, and Coble (1998) and Wallach, Safir, and Bar-Zvi (2009)).…”
Section: Studymentioning
confidence: 95%
“…Use of virtual reality is gathering momentum in adult stress testing and is suggested as an effective alternative (Montero-Lopez et al, 2015;Wallergard et al, 2011). A pre-recorded audience was applied in the Leiden public speaking task with a panel of adolescents in a classroom setting, eliciting a moderate stress response in adolescents aged 12-15 years (Westenberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%